Program to Support Life (PRAVIDA): Integrating Research, Intervention and Education for Suicide Prevention - Ribeiro Pinho de Sousa, Nathalia; Carvalho de Souza, Barbara; Mourão de Aquino Neto, José; Ribeiro Gomes, Maria Hortencia; Lacerda Borges de Sá, Inis Stella; Araújo Teixeira, Luidianne Karoline; Gomes de Matos e Souza, Fábio (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2014)
Suicide constitutes an important global public health issue. The World Health Organization (WHO) estimates that global suicide mortality increased about 60% in the last 45 years. Among all 27 Brazilian states, Ceará occupies the 9th position in rates of suicide and Fortaleza, its state capital, had the 4th highest suicide rate among Brazilian capitals, between entre 2004 and 2006. The aim of PRAVIDA (Programa de apoio à vida - Program to support life) is to prevent suicide through therapeutic assistance, dissemination of information and research about suicide. The objective is to present the pioneering experience of PRAVIDA regarding the therapeutic care of patients with suicidal ideation or attempted suicide. Therefore, PRAVIDA intends to establish partnerships to facilitate new strategies to prevent suicide and improve the knowledge on the topic, stimulating appreciation of life, the host and the listening subject who seek medical treatment in the program.